Strategi Pengembangan Koperasi Di Indonesia Melalui Pendekatan Kerangka Berpikir Logis - Lulus Setiawan, Wawan (Coopetition : Jurnal Ilmiah Manajemen, 2025)
Cooperatives in Indonesia play a crucial role in supporting the informal sector and improving community welfare. Various strategies have been implemented to develop cooperatives in Indonesia. However, several challenges, such as low member participation, weak governance, and limited capital, hinder their progress. Therefore, this study aims to examine the problems faced by cooperatives in Indonesia. The research adopts the Logical Framework Approach (LFA) to systematically analyze cooperative development strategies. This approach includes identifying key issues, formulating objectives, developing alternative solutions, and constructing a logical matrix for planning. The findings reveal that several major challenges faced by cooperatives can be addressed through integrated strategies. These strategies include strengthening human resource capacity through management training, improving access to capital via partnerships with financial institutions, adopting digital technology for operational transparency, and providing incentives for member participation. Moreover, collaboration between the government, cooperative members, financial institutions, and academics is key to the successful implementation of these strategies. Keywords:  Cooperatives,  Logical  Framework  Approach,  Member  Participation, Digitalization, Development Strategies